Computational Study of Nocardiotide-A Analogues in the Development of Technetium-99m Radiopeptides for Cancer Imaging for Targeting Somatostatin Receptor 2 - Rizky Juwita Sugiharti; Rani Maharani; Rahmana Emran Kartasasmita; Daryono Hadi Tjahjono (Directorate for Research and Community Services (LPPM) ITB, 2023)
Nocardiotide-A (cWIWLVA) is a cyclic peptide with significant cytotoxicity against several cancer cells. The present research aimed to design a radiopeptide based on nocardiotide-A analogues to be labeled by technetium-99m targeting SSTR2, which is the most widely expressed receptor in several types of human cancers and used as radiopeptide target. Nocardiotide-A analogues were individually designed by replacing valine at the lead compound with lysine, arginine, histidine, asparagine, and glutamine, and this was simulated by molecular dynamics using AMBER18. A molecular docking using AutoDock 4.2 was performed and evaluated to understand the effect of chelation of technetium-99m on 99mTc-HYNIC-EDDA and 99mTc-HYNIC-tricine on the binding affinity of nocardiotide-A analogues. The molecular dynamics simulation confirmed that the designed nocardiotide-A-based peptides were stable in the binding pocket of SSTR2 for 200 ns. Moreover, the nocardiotide-A-based radiopeptides are able to interact with residues Q102, D122, Q126, and N276 by building hydrogen bonds, which are essential binding residues in SSTR2. The molecular docking simulation revealed that the best docking parameter is exhibited by 99mTc/EDDA/HYNIC-cWIWLNA and 99mTc/tricine/HYNIC-cWIWLNA with a binding free energy of –12.59 kcal/mol and –8.96 kcal/mol, respectively. Taken together, nocardiotide-A-based radiopeptides are prospective to be further developed for cancer imaging targeting SSTR2.